‘Make Sure You Don’t Murder Your Coffee!’ Comedy and Violence in the Poetry of Luke Kennard - Paul McDonald (Sillages Critiques)
This paper discusses the relationship between comedy, violence, and postmodernism in the work of the British poet, Luke Kennard. It has been argued that British poets of the twentieth century have an ambivalent relationship with postmodernism because, while they accept that certainty is elusive, they refuse to ignore meaning and value, and their writing frequently exhibits “an ethical demand.” I claim that this can also be said of Kennard’s twenty first century postmodernist writing. In an analysis of his popular poem, ‘The Murderer,’ I show that what initially seems to be a typically postmodern, morally disengaged treatment of violence, also employs characteristics associated with traditional comedy, and the combination of the two modes of humour creates a space in which values can be reclaimed.